Front Cover: Correlation between the Dynamics of Nanoconfined Water and the Local Chemical Environment in Calcium Silicate Hydrate Nanominerals (Chem. Eur. J. 44/2021). Issue 44 (26th June 2021) - Musumeci, Valentina; Goracci, Guido; Sanz Camacho, Paula; Dolado, Jorge S.; Aymonier, Cyril
Abstract : The ultra‐fast synthesis of calcium silicate hydrates was performed in supercritical water that acts as a solvent for mimicking the natural conditions at high pressure and high temperature of the geological process. The synthesised xonotlite and tobermorite represent perfect Ca−OH‐rich and Si−OH‐rich model nanocrystals for investigating the effect of different chemical environments on the dynamics of confined water. These results could be applied to other water‐containing construction materials. More information can be found in the Full Paper by J. S. Dolado, C. Aymonier et al. (DOI: 10.1002/chem.202100098 ).